Zoogeography, taxonomy, and conservation of West Virginia’s Ohio River floodplain crayfishes (Decapoda, Cambaridae) - Zachary Loughman; Thomas Simon (ZooKeys, 2011)
The crayfish fauna of West Virginia consists of 23 species and several undescribed taxa. Most survey efforts documenting this fauna have been conducted in lotic waterways throughout the Appalachian plateau, Allegheny Mountains, and Ridge and Valley physiographic provinces. Bottomland forests, swamps, and marshes associated with large river floodplain such as the Ohio River floodplain historically have been under-surveyed in the state. These habitats harbor the richest primary burrowing crayfish fauna in West Virginia, and are worth of survey efforts. In an effort to fill this void, the crayfish fauna of West Virginia’s Ohio River floodplain was surveyed from 2004 through 2009. From this survey, nine species from four genera were documented inhabiting the floodplain. Zoogeography, biology, and conservation status is provided for all nine crayfi shes. The dominant genus along the floodplain is Cambarus, which includes Cambarus (C.) carinirostris, Cambarus (C.) b. cavatus, Cambarus (P.) robustus and Cambarus (T.) thomai. Cambarus (T.) thomai is the most prevalent burrowing species occurring along the floodplain. The genus Orconectes consists of two native species, Orconectes (C.) obscurus and Orconectes (C.) s. sanbornii; and two invasive taxa, Orconectes (G.) virilis and Orconectes (P.) rusticus. Orconectes (C.) obscurus has experienced a range extension to the south and occupies streams formerly occupied by O. (C.) s. sanbornii. Both invasive taxa were allied with anthropogenic habitats and disturbance gradients. Th e genera Fallicambarus and Procambarus are represented by a single species. Both Fallicambarus (C.) fodiens, and Procambarus (O.) acutus are limited to the historic preglacial Marietta River Valley.